Digital Transformation and National Security Ensuring - Кормич, Людмила Іванівна; Кормич, Л. І.; Kormych, Liudmyla I.; Краснопольська, Тетяна Миколаївна; Краснопольська, Т. М.; Krasnopolska, Тetiana М.; Завгородня, Юлія Володимирівна; Завгородня, Ю. В.; Zavhorodnia, Yuliia V. (Praha : Enigma Corporation, 2024)
The article analyzes the essence and consequences of digital transformation in modern society for the national security system. It is shown that the digital transformation that takes place in modern conditions actively affects the area of national security. It is proved that, on the one hand, it acts as a contributing factor to national security, since it increases the efficiency of public administration, and, being the main driver of reforms in this field, transforms the public policy system, leads to an expansion of citizens’ political participation, and therefore democratizes public life. Also, digitalization expands the possibilities of influencing officials and other ambassadors of the state on foreign public opinion through digital public diplomacy. Moreover, the introduction of digital technologies may increase the level of economic development of the state. On the other hand, digital transformation poses several new threats to national security, namely in the economic, social, and information space. It contributes to digital political isolation, the shift of political activity in the digital environment and the emergence of new virtual unconventional forms of political participation, the development of cyber threats and cyberattacks, etc. It is substantiated that the formation of a comprehensive national security system in the conditions of digital transformation will contribute to overcoming the threats of digitalization, the key development vectors, which in Ukraine include economic, information, and cybersecurity. It is proved that using the tools of these forms of security will help overcome the negative effects of digitalization and reinforce its positive role in society. It is well-founded that digitalization is a new progressive process in government activity, with challenges and threats developing in cyberspace. An important component for the development of digitalization in developing countries is low material and transaction costs.
Kormych L. Digital Transformation and National Security Ensuring / L. Kormych, T. Krasnopolska, Yu. Zavhorodnia // Evropsky Politicky a Pravni Diskurz. – Praha : Enigma Corporation, 2024. – 11(1). – P. 29-37. URL: https://doi.org/10.46340/eppd.2024.11.1.4
Keywords: digitalization; digital transformation; national security; information security; cyber security; economic security; public diplomacy; digital diplomacy